Teacher evaluation programs. A way of being a teacher-researcher at Universidad Autónoma del Estado de México - González Villanueva, Leonor; Fabila Pérez, Jacqueline; Islas Corona, Edy (IE Revista de Investigación Educativa de la REDIECH, 2025)
The study of evaluation programs (recognition and/or encouragement of academic performance) of Higher Education (HE) teachers is part of the educational agenda due to the impact they have had on teaching, the dynamics of institutions and the higher education system. The objective of this research was to analyze the reasoning systems that underlie and are configured within the framework of teacher evaluation programs that order the “what to do?” and the “how to do?” of full-time professors of the Universidad Autónoma del Estado de México (UAEM). The political sociology of knowledge allows to explain evaluation as a historical discourse that embodies reasoning systems. Academic production was analyzed from a qualitative descriptive approach. The main results show that the research carried out by full-time professors is short-term and tends to reproduce current knowledge systems. The publication strategy is predominantly massive and collective. Research and academic production are weakly linked to teaching. The system of reason proposed by the evaluation programs is reinterpreted by the professors, giving way to the emergence of new ways of being a teacher-researcher.